Analyzing the Initiation- Response and Feedback Patterns and Its Impact on the Interaction between Teacher and Students in English Classroom - Eka Barahma Putri; Machdalena Vianty; Sary Silvhiany (Universitas Jambi, Indonesia, 2021)
This study was based on the phenomenon of classroom interaction in enhancing students’ language skills in English classes using the 2013 curriculum. This study investigated the dominant initiation- response and feedback [IRF] patterns and its impact on the interaction between the teacher and the tenth-grade students during classroom spoken discourse. This qualitative research involved a teacher of English and four classes. The data were collected via classroom observations and semi-structured interviews. The findings of the study showed that in the IRF pattern, the most dominant pattern was initiation. The teacher dominated the classroom during the lesson and the IRF pattern had positive impacts on students’ English when the teacher asked questions. The teacher needed to understand what questions students needed to ask to respond well because it must be in line with the 2013 curriculum, which places students at the center of learning. Teachers needed to use more various feedbacks from the IRF pattern. It can be seen from the observation that the teacher did not use feedback much when students responded to the initiation from the teacher because feedback is essential to increase student motivation, confidence, and evaluation.